1999
DOI: 10.1897/1551-5028(1999)018<2023:sdator>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular Distribution and Translocation of Radionuclides in Plants

Abstract: The subcellular distribution of radionuclides in Glycine max Merr. (soybean) and Cucumis sativus L. (cucumber) and translocation of plant absorbed radionuclides with growth in soybean were studied. More than 60% of cellular incorporated Rb, Sr, Mn, Co, Nb, and Se remained in the supernatant fraction; 55% and 20% of Cr was bound to soybean and cucumber cell wall fractions, respectively; 70% or more of Be, Y, and Fe was fixed in the chloroplast fraction; and approx. 10% of Sc, Fe, V, and As were fixed in the mit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
2
1
0
Order By: Relevance
“…On the other hand, 109 Cd migrated only a small distance and most of the radioactivity was found at harvest only in organs close to the contamination point (i.e., stems, bean leaves located on the same trifoliate leaf as the spiked leaf), in accordance with the observations of Bengtsson (1992), Carini et al (1999), and Katana et al (1998) on 85 Sr. No 109 Cd was detected in bean seeds following foliar contamination. These results are in accordance with the works of Baldini et al (1987) and Monte et al (1990) on 137 Cs and 103 Ru, Bengtsson (1992) and Zehnder et al (1995) on 134 Cs and 85 Sr, and Gouthu et al (1999) on Rb, Zn, Fe, Nb, Cr, and Sc, who demonstrated that mobile radionuclides (Cs, Zn, Fe, and Rb) accumulated mainly in the fruit of trees after foliar contamination (in average 25% of the intercepted radioactivity), while radionuclides with a low mobility (Nb, Cr, Sc, Sr) were not present in the fruit. In the same way, Bittel and Clément (1965), Gerdung et al (1999), and Middleton and Squire (1963) showed a translocation of mobile 134 Cs from potato leaves to tubers (storage organ) similar to the 63 Ni translocation observed in our experiment from radish leaves to filling storage roots (20–50% in the potato tubers and 19 ± 2% to 36 ± 4% in the radish roots).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…On the other hand, 109 Cd migrated only a small distance and most of the radioactivity was found at harvest only in organs close to the contamination point (i.e., stems, bean leaves located on the same trifoliate leaf as the spiked leaf), in accordance with the observations of Bengtsson (1992), Carini et al (1999), and Katana et al (1998) on 85 Sr. No 109 Cd was detected in bean seeds following foliar contamination. These results are in accordance with the works of Baldini et al (1987) and Monte et al (1990) on 137 Cs and 103 Ru, Bengtsson (1992) and Zehnder et al (1995) on 134 Cs and 85 Sr, and Gouthu et al (1999) on Rb, Zn, Fe, Nb, Cr, and Sc, who demonstrated that mobile radionuclides (Cs, Zn, Fe, and Rb) accumulated mainly in the fruit of trees after foliar contamination (in average 25% of the intercepted radioactivity), while radionuclides with a low mobility (Nb, Cr, Sc, Sr) were not present in the fruit. In the same way, Bittel and Clément (1965), Gerdung et al (1999), and Middleton and Squire (1963) showed a translocation of mobile 134 Cs from potato leaves to tubers (storage organ) similar to the 63 Ni translocation observed in our experiment from radish leaves to filling storage roots (20–50% in the potato tubers and 19 ± 2% to 36 ± 4% in the radish roots).…”
Section: Discussionsupporting
confidence: 92%
“…In contrast, 109 Cd was moderately mobile in the plants. Nickel is known to be highly mobile in the phloem, because it occurs in plant metabolism as a component of the urease enzyme (Neumann and Chamel, 1986), whereas 109 Cd was shown to migrate weakly and slowly and to accumulate on/in the aerial contaminated organs (De Cormis, 1968; Gouthu et al, 1999; Romney et al, 1969). The bivalence of the 63 Ni ion did not seem to constitute a limit to its migration, although Russel (1966) mentioned that bivalent ions are less mobile than monovalent ones.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, according to our results, the second highest Sr level accumulated and remained in fruit stalks. These results are in agreement with those reported by Gouthu et al [ 74 ], who studied Sr translocation in soybean and found the highest Sr contents in plant leaves and the lowest in flowers and fruits. Since Sr is a poorly phloem-mobile element that is distributed in plants mainly though the xylem [ 1 ], its contents in flowers and fruits are low.…”
Section: Resultssupporting
confidence: 93%